MAKNA BENTUK VISUALISASI KEINDAHAN TOPENG PANJI DAN KLANA - Al Aziz, Iqbal Syahrul Akbar (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2023)
Abstract: Indonesia has many diverse cultures, one of which is masks. The mask is a cultural and spiritual cultural heritage that functions as a face covering. This study aims to describe the ocular meaning of the character structure of the masks of Panji Asmarabangun and Klana Sewandana which includes the appearance of the two masks as objects. This research will focus more on the visualization meaning of Panji and Klana masks through discursive symbols. The approach used is a structuralism approach and a symbolic interpretation of culture. The method in this study used a qualitative descriptive method. Data were collected through observational techniques and analyzed by Miles and Huberman's interactive theory from three stages, one of which was data reduction. Data reduction can be used by summarizing, then identifying the data that is the subject of discussion in the researcher. After that, the researcher presents the data, and draws conclusions until the data is completely saturated. The results of this study indicate that the Panji Asmarabangun mask has a good character embodiment in terms of aesthetics and meaning in the shape of the mask. Meanwhile, the Klana Sewandana mask has the embodiment of an evil character, full of anger through the interpretation of the aesthetic form of the mask.